2020
DOI: 10.5194/acp-20-8139-2020
|View full text |Cite
|
Sign up to set email alerts
|

Combining atmospheric and snow radiative transfer models to assess the solar radiative effects of black carbon in the Arctic

Abstract: Abstract. The magnitude of solar radiative effects (cooling or warming) of black carbon (BC) particles embedded in the Arctic atmosphere and surface snow layer was explored on the basis of case studies. For this purpose, combined atmospheric and snow radiative transfer simulations were performed for cloudless and cloudy conditions on the basis of BC mass concentrations measured in pristine early summer and more polluted early spring conditions. The area of interest is the remote sea-ice-covered Arctic Ocean in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The Polar Airborne Measurements and Arctic Regional Climate Model simulation Project (PAMARCMiP) 2018 aircraft-based field experiment was carried out around the northern Greenland Sea (Fram Strait) from 23 March to 4 April 2018 using Station Nord (81.6 • N, 16.7 • W) as the operation base (Herber et al, 2012(Herber et al, , 2019Donth et al, 2020;Koike et al, 2021), as part of the ArctiC Amplification: Climate Relevant Atmospheric and SurfaCe Processes, and Feedback Mechanisms or (AC) 3 project (Wendisch et al, 2017). In this paper, we report vertical profiles of BC mass concentrations, size distributions, and mixing states measured using a single-particle soot photometer from The University of Tokyo (Yoshida et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Polar Airborne Measurements and Arctic Regional Climate Model simulation Project (PAMARCMiP) 2018 aircraft-based field experiment was carried out around the northern Greenland Sea (Fram Strait) from 23 March to 4 April 2018 using Station Nord (81.6 • N, 16.7 • W) as the operation base (Herber et al, 2012(Herber et al, , 2019Donth et al, 2020;Koike et al, 2021), as part of the ArctiC Amplification: Climate Relevant Atmospheric and SurfaCe Processes, and Feedback Mechanisms or (AC) 3 project (Wendisch et al, 2017). In this paper, we report vertical profiles of BC mass concentrations, size distributions, and mixing states measured using a single-particle soot photometer from The University of Tokyo (Yoshida et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…8,17,18 For example, Hansen and Nazarenko 8 provided a plausible snow albedo forcing estimate of +0.3 W m −2 (TOA) for the Northern Hemisphere (NH), whereas Flanner et al 17 reported a global mean annual BC/snow-surface RE of 0.007–0.12 W m −2 , which is considerably lower than estimates (5–10 W m −2 ) for Northern China reported by Zhao et al 18 Although the atmospheric BC-DRF and BC snow albedo elements have been investigated separately in these previous studies, to date, little attention has been paid to the total radiative effect of BC in both the atmosphere and snow cover concurrently. 19…”
Section: Introductionmentioning
confidence: 99%
“…8,17,18 For example, Hansen and Nazarenko 8 provided a plausible snow albedo forcing estimate of +0.3 W m À2 (TOA) for the Northern Hemisphere (NH), whereas Flanner et al 17 reported a global mean annual BC/ snow-surface RE of 0.007-0.12 W m À2 , which is considerably lower than estimates (5-10 W m À2 ) for Northern China reported by Zhao et al 18 Although the atmospheric BC-DRF and BC snow albedo elements have been investigated separately in these previous studies, to date, little attention has been paid to the total radiative effect of BC in both the atmosphere and snow cover concurrently. 19 Existing uncertainties in the BC-RE are relatively large, owing to external factors including the surface albedo, water vapor, and, most notably, the presence of clouds and the vertical distribution of BC. [19][20][21] For instance, Haywood and Shine 22 revealed that the presence of highly reective clouds beneath BC aerosol layers can dramatically enhance the overall RE of the atmospheric BC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reality, the parameters determining the albedo of snow-covered surfaces are manifold, such as the solar zenith angle (SZA), cloudiness, snow impurities, surface roughness, snow grain size and shape [10][11][12][13][14][15][16][17][18]. E.g., Donth et al [19] quantified the effect of black carbon (BC) impurities, cloudiness, and snow grain size on the broadband snow surface albedo (α bb ). They identified a minor BC effect (∆α bb = 0.01 for a reasonable range of BC mass concentration in snow), but major effects due to cloudiness (∆α bb up to 0.12 for aged snow) and snow grain size (∆α bb = 0.07 for particles of fresh and aged snow).…”
Section: Introductionmentioning
confidence: 99%